Nutrient and immune sensing are obligate pathways in metabolism, immunity, and disease. Issue 9 (11th June 2015) - Iyer, Abishek; Brown, Lindsay; Whitehead, Jonathan P.; Prins, Johannes B.; Fairlie, David P.
ABSTRACT: The growth and survival of multicellular organisms depend upon their abilities to acquire and metabolize nutrients, efficiently store and harness energy, and sense and fight infection. Systems for sensing and using nutrients have consequently coevolved alongside systems for sensing and responding to danger signals, including pathogens, and share many of the same cell signaling proteins and networks. Diets rich in carbohydrates and fats can overload these systems, leading to obesity, metabolic dysfunction, impaired immunity, and cardiovascular disease. Excessive nutrient intake promotes adiposity, typically altering adipocyte function and immune cell distribution, both of which trigger metabolic dysfunction. Here, we discuss novel mechanistic links between metabolism and immunity that underlie metabolic dysfunction in obesity. We aim to stimulate debate about how the endocrine and immune systems are connected through autocrine, paracrine, and neuroendocrine signaling in sophisticated networks that are only now beginning to be resolved. Understanding the expression and action of signaling proteins, together with modulating their receptors or pattern recognition using agonists or antagonists, will enable rational intervention in immunometabolism that may lead to novel treatments for obesity and metabolic dysfunction.—Iyer, A., Brown, L., Whitehead, J. P., Prins, J. B., Fairlie, D. P. Nutrient and immune sensing are obligate pathways in metabolism, immunity, and disease. FASEB J. 29, 3612‐3625 (2015). www.fasebj.org